Head Nurses’ Management Regarding Patient Safety in Public Hospitals Aceh Province, Indonesia - Yuswardi, Yuswardi; Nongnut Boonyoung; Pratyanan Thiangchanya (Fakultas Keperawatan-Universitas Syiah Kuala, 2015)
ABSTRACTHead nurses play a major role in managing patient safety. To what extent head nurses in Aceh province, Indonesia here applied patient safety goals as standard guiding their management. This study aimed to identify the levels of head nurse’ management regarding patient safety in public hospitals Aceh, Indonesia. A descriptive study was conducted in fourteen public hospitals in Aceh province, Indonesia. A proportionate stratified random sampling technique was used to recruit 123 head nurses from 14 out of 21 hospitals of three geographical areas of Aceh province. The data collection instruments were developed by the researchers, based on 6 areas of the JCI’s patient safety goals statements and displaying use of the PDCA cycle in managing patient safety. The study conducted from January to March 2013. The overall score of head nurses’ regarding patient safety was at a high level. Management of each dimension including identifying patient correctly (M = 4.39, SD = 0.51), improving effective communication (M = 4.11, SD = 0.60), maintaining safety of high alert medication (M = 4.16, SD = 0.65), ensuring correct procedure (M = 4.02, SD = 0.69), reducing the risk of healthcare associated infections (M = 3.71, SD = 0.79) and reducing risk from fall (M = 3.71, SD = 0.91) respectively. The high level of head nurses’ management regarding patient safety may lead to reduce adverse patient event, error, and mortality. Management of adverse event was a strategy to ensure patient safety during hospitalization.Keyword: Head nurse, management, patient safety, public hospital.